2020
DOI: 10.1111/phpp.12558
|View full text |Cite
|
Sign up to set email alerts
|

Pupils' use of school outdoor play settings across seasons and its relation to sun exposure and physical activity

Abstract: Background Long outdoor stay may cause hazardous exposure to ultraviolet radiation (UVR) from the sun even at high latitudes as in Sweden (Spring to Autumn). On the other hand, long outdoor stay is a strong predictor of primary school children´s free mobility involving moderate to vigorous physical activity (MVPA). UV‐protective outdoor environments enable long outdoor stay. We investigated the concurrent impact of different school outdoor play settings upon pupils´ sun exposure and levels of physical activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Given the prominent role seasons play in the Nordic countries, seasonal variation has received little attention in relation to adolescent outdoor life. The study revealed that adolescents spent significantly more time outdoors during spring/summer compared to autumn/winter, which is in line with the well-documented decline in outdoor activity and physical activity during colder months (Pagels et al, 2020;Zheng et al, 2021). Nonetheless, there was a significant positive association between perceived environmental quality and well-being, even during autumn/winter.…”
Section: Adolescents' Perceptions and Use Of Outdoor Environments Acr...supporting
confidence: 82%
“…Given the prominent role seasons play in the Nordic countries, seasonal variation has received little attention in relation to adolescent outdoor life. The study revealed that adolescents spent significantly more time outdoors during spring/summer compared to autumn/winter, which is in line with the well-documented decline in outdoor activity and physical activity during colder months (Pagels et al, 2020;Zheng et al, 2021). Nonetheless, there was a significant positive association between perceived environmental quality and well-being, even during autumn/winter.…”
Section: Adolescents' Perceptions and Use Of Outdoor Environments Acr...supporting
confidence: 82%
“…However, grip strength has been associated with schoolyard size or equipment type (26,27); an intervention that modified the outdoor space led to changes in grip strength (28). Similarly, where children play outdoors moderates the relationship with vitamin D level (29), whereas environmental features like greenery or air pollution may be important to capture for blood pressure or C-reactive protein, respectively (6,30). Capturing PA type and intensity may be important as vigorous-intensity activity and unusual strain distributions that are afforded during recess are integral to the modification of bone mineral content (4), and anthropometrics have been related to moderate- to vigorous-intensity PA (31).…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on the November 1 to April 30 period may have weakened associations between recess provision and some outcomes; for example, outdoor time is not the primary source of vitamin D during this period, and shorter daylight hours reduce opportunity for outdoor time outside school (29). This temporal restriction also reduced our sample size, and our inclusion of effect sizes revealed that recess provision may have only small associations, which we would be underpowered to detect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation